Comparative Analysis of Intravenous Ceftriaxone and Ciprofloxacin for the Treatment of Bacterial Peritonitis in Liver Cirrhosis - Arbab Muhammad Kashif Khan, Mohsina Haq, Rahman Shah, Saifullah Khan Khalil, Nasir Bakhtiar, Fahd Masud, Hikmat Ullah, Qudrat Ullah Khan, Amir Ullah Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
The Purpose of the current study to Evaluate the efficacy of intravenous ciprofloxacin with ceftriaxone for the treatment of bacterial peritonitis in patients of liver cirrhosis at PIMS Hospital Islamabad from January 2021 to June 2021 at Department of Medicine .A total of 260 patients of liver cirrhosis were selected for this study. Patients were randomly allocated in two groups (Group A and B). Patients aged 13 to 60 years of both genders with established liver cirrhosis, diagnosed on ultrasound abdomen were included in this study. Patients with hemorrhagic or malignant ascites, peritonitis, tuberculosis peritonitis, hepatocellular carcinoma and diabetes mellitus were excluded from study. In group A, 130 patients were given intravenous ciprofloxacin 200mg 12 hourly and in group B 130 patients on ceftriaxone 1g 12 hourly. Treatment was given for 5 days and efficacy of treatment was determined by means of evaluating clinical symptoms. The mean age of the patients in group A was 43.4±10.4 years and in group B was 44.2±10.2 years. In group A there were 90(70%) patients and 95(73.3%) patients in group B in whom spontaneous bacterial peritonitis was settled down. The Result of the current study suggest that Intravenous is as effective as ceftriaxone in the treatment of spontaneous bacterial peritonitis in cirrhotic patients. Keywords: liver cirrhosis, ciprofloxacin, bacterial peritonitis, ceftriaxone